Privatization in Denmark, 1980-2002 - Henrik Christoffersen; Martin Paldam (Center for Economic Studies and ifo Institute (CESifo), 2004)
Denmark is one of the most developed welfare states, but also a rather capitalistic state with little public ownership outside the traditional fields of the public sector and the natural monopolies of the network industries. The low level of public ownership corresponds to peoples' attitude in polls. Nevertheless, 12 privatizations of state companies have been made along with everybody else. No statistics on privatization have been previously published in Denmark. Most of the 12 privatizations are small, and the telephone company provides 76 percent of the total revenue. In the municipal sector, however, most privatization activity appears to be outsourcing.
Keywords: 330; Privatization; outsourcing; capitalist values